The mediating effect of geospatial thinking on the relationship between family capital and sense of place - Zhang, Jianzhen; Liang, Xiaoyu; Su, Ting; Li, Xinyao; Ge, Jiahao; An, Zhenni; Xu, Yanhua (Frontiers in Psychology, 2022)
To understand the relationship between family capital and sense of place and the mechanisms at work within this relationship, this study constructs a mediation model to examine the impact of family capital on their sense of place and the mediation effect of geospatial thinking. A total of 1,004 upper-secondary-school students were surveyed using the Family Capital Questionnaire, the Geospatial Thinking Test, and the Sense of Place Scale. SPSS (version 26.0) was used for descriptive statistical analysis and correlation analysis. The PROCESS plug-in (version 4.0) was used to test the mediating effect of geospatial thinking. The correlation analysis showed that family capital has a positive effect on sense of place and is related to geospatial thinking. Moreover, geospatial thinking exerts a positive effect on sense of place. The results of mediation analysis indicated that geospatial thinking plays mediating and buffering roles in the relationship between family capital and sense of place after controlling for gender and residential address. The direct and indirect effects accounted for 73.31% and 26.69% of the total effect, respectively. Specifically, geospatial thinking was found to be a partial mediator and play a buffering role between family capital and sense of place. Therefore, it is necessary to pay attention to the role of family in the development of sense of place. In addition, developing geospatial thinking is also critical to enhancing students' sense of place.